Current Situation and Countermeasures of Education Quality Assurance for International Students in Guangxi Universities - Miao, Zhibin; Cong, Xiaohong; Pang, Qishuo; Zhang, Wenbo; Shi, Ruize (Education Insights, 2026)
As a strategic bridgehead between China and the Association of Southeast Asian Nations (ASEAN), Guangxi possesses abundant resources and unique geographical advantages in fostering international academic exchanges. Consequently, the region has historically attracted numerous international students from ASEAN countries and other global regions, significantly contributing to regional educational integration. However, in the wake of shifting global dynamics and post-pandemic realities, universities in Guangxi are currently facing multifaceted challenges. These include a noticeable decline in the enrollment of international students, structural difficulties in adapting traditional training models to diverse cultural backgrounds, and the persistence of outdated administrative management methods. There is an urgent need to systematically strengthen education quality assurance mechanisms for international students to meet the rigorous development requirements under the new globalized educational situation. This paper comprehensively analyzes both the internal and external factors affecting education quality assurance for international students in Guangxi universities. Internally, it examines institutional infrastructure, curriculum design, and faculty intercultural competence. Externally, it evaluates macroeconomic policies, geopolitical shifts, and cross-border mobility constraints. Furthermore, this study discusses strategic countermeasures and actionable suggestions for improving the overall level of education quality assurance. By proposing innovative management frameworks, tailored pedagogical approaches, and enhanced feedback systems, this research aims to provide a robust theoretical foundation and practical guidelines for Guangxi universities to revitalize their international education programs and sustain long-term competitiveness.